The Utilization of Waste Pieces of Wood as Materials for Making Children's Study Tables - Zahriana; Maulina, Dian; Ben, Hasbaini; Mislina; Saputra, Devi Satria (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2023)
Wood waste was waste from the wood production process which can be in the form of chips or remaining pieces of wood. Based on these data, processed wood scrap waste can be used as an industrial product in the form of a children's study table, while the remaining wood waste that has been disposed of so far has been left to rot, stacked and burned, resulting in a negative impact on the environment. The problem in this research was how to make a children's study table from waste pieces of wood. The aim of the study was to make a children's study table from waste pieces of wood, while the method used was an experimental method using 2 samples with different material compositions. The result of the research was that a children's study table was made which has a length of 60 cm and a height of 25 cm. Then the conclusion of the study resulted in a children's study table product from wood scrap waste.